Lat’s comics and the articulation of the Malaysian cultural landscape - Lee, Siew Chin; T'ng Cheah, Kiu Choon; Noraza Ahmad Zabidi,; Badrul Redzuan Abu Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Over the past few years, there has seen some renewed serious interest in comics in terms of the humour and narrative aspect. However not much can be said of comics as a representation of the cultural mores of the community. This study looks at how a local comic writer frames his subjective viewpoints, and how he stages them graphically and visually in his comics. Using Rodriguez and Dimitrova’s (2011) four-tiered model, this paper sets out to analyse how Lat frames culture in his comics in 5 selected comic strips culled from online sources. The findings indicated that Lat has a tendency to frame his cartoons in terms of a Malaysianised landscape. Of interest is the way in which he portrays the Malaysian as a melting pot of multi-cultural community through a sharp and yet seemingly tongue-in-cheek portrayal of their values and behaviours.